Coaches' perceptions of competence and acknowledgement of training needs related to professional competences - Santos, S.; Mesquita, I.; Graca, A.; Rosado, A. (Journal of Sports Science & Medicine, 2010)
The purpose of the present study was to examine coaches' perceptions of competence and acknowledgement of training needs related to professional competences according to the professional experience and academic education. The participants were 343 coaches from several sports, who answered to a questionnaire that includes a scale focused on perceptions of competence and another scale on acknowledgment of training needs. An exploratory factor analysis with Maximum Likelihood Factoring was used with Oblimin rotation for the identification of emergent factors. Comparison on coaches' perceptions in function of coaching experience and coaches' academic background were made applying One-way ANOVA and Tukey's post hoc multiple comparisons. Factor analysis on coaches' perceptions of competence and acknowledgement of training needs made apparent three main areas of competences, i.e. competences related to annual and multi-annual planning; competences related to orientation towards practice and competition; and personal and coaching education competences. Coaches' perceptions were influenced by their experience, as low experienced coaches rated themselves at lower levels of competence and with more training needs; also coaches with high education, in Physical Education or others, perceived themselves as more competent than coaches with no higher education. Finally, the majority of the coaches perceived themselves to be competent but, nevertheless, they indicated to have training needs, which brings an important feedback to coach education. This suggests that coaches are interested in increasing their knowledge and competence in a broad range of areas which should be considered in future coach education programs.